2016
DOI: 10.5505/tjtes.2016.37897
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Instant Messaging Application in Coordination of Emergency Calls for Combat Injuries: A Pilot Study

Abstract: BACKGROUND: Coordination of an emergency response team is an important determinant of prompt treatment for combat injuries in hospitals. The authors hypothesized that instant messaging applications for smartphones could be appropriate tools for notifying emergency response team members. The objective of this study was to investigate the efficiency of a commercial instant messaging application (WhatsApp, Mountain View, CA) as a communication tool for the emergency team in a level-I trauma center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Use of instant messaging apps was mostly perceived and evaluated as useful/essential or useful but not mandatory and the perception of negative impacts on medical practice was remarkably low. Most of the participants had not seen any literature-based evidence regarding the use of these apps.The fact that most of the participants declared that they were using WhatsApp and Facebook Messenger corroborates descriptions in the literature of what the most popular mobile messenger apps within the field of medicine are, worldwide [12][13][14][15]. Since the 1990s, these technologies have changed daily human activities, not only individually or economically, but also socially.…”
supporting
confidence: 72%
“…Use of instant messaging apps was mostly perceived and evaluated as useful/essential or useful but not mandatory and the perception of negative impacts on medical practice was remarkably low. Most of the participants had not seen any literature-based evidence regarding the use of these apps.The fact that most of the participants declared that they were using WhatsApp and Facebook Messenger corroborates descriptions in the literature of what the most popular mobile messenger apps within the field of medicine are, worldwide [12][13][14][15]. Since the 1990s, these technologies have changed daily human activities, not only individually or economically, but also socially.…”
supporting
confidence: 72%
“…For example, the introduction of tools to facilitate smoother communication, such as smartphone applications, might be an option to solve this problem. [ 31 ] Introduction of EMS vehicles with a doctor (eg, a doctor's car and doctor's helicopter) could also improve EMS systems instead of carrying patients to distant medical facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have tested Apps like Siilo and WhatsApp for effectiveness in instant communication and consulting during patient management demonstrating faster and efficient mode of contact for the caregivers [ 38 , 39 ]. Furthermore, clinical monitoring Apps, intensive care units Apps, decision-making Apps in radiology units have together revolutionized digital healthcare facilitating quicker communication and improved patient management [ 40 42 ]. The functionalities of the proposed naive STEMI App follow an integration of the aforementioned components.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have demonstrated the effectiveness of using mobile applications and instant messaging for faster and accurate inter-team communication facilitating emergency alert [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%